Risk factors associated with stunting among toddlers aged 24–59 months: A Case-Control - Sada, Kumbendy; Zakaria, Zakaria; Rifai, Muhammad (Jurnal Ilmiah Kesehatan Sandi Husada, 2025)
Introduction: Stunting remains a major public health concern in Indonesia, particularly in remote and highland regions such as the Bintang Mountains of Papua. It is characterized by impaired physical and cognitive development due to chronic malnutrition, repeated infections, and inadequate health services. Understanding the determinants of stunting in these settings is critical to inform effective interventions and policies. Methods: This study employed an analytical survey with a case-control design to examine risk factors associated with stunting among toddlers aged 24–59 months in the Oksibil Health Center working area, Bintang Mountains Regency, Papua. A total of 66 respondents were recruited between April and May 2024, consisting of 33 stunted toddlers (cases) and 33 non-stunted toddlers (controls). Data were collected through structured interviews and analyzed using odds ratios (ORs) with 95% confidence intervals to identify significant risk factors. Results: The findings revealed that several factors were significantly associated with stunting: maternal knowledge (OR = 1.911), history of infectious diseases (OR = 8.090), environmental sanitation (OR = 1.375), socio-cultural practices (OR = 3.801), and health service utilization (OR = 9.339). Among these, inadequate health service utilization posed the highest risk. Socio-cultural norms, poor hygiene practices, and limited maternal awareness were also strongly linked to stunting prevalence. Conclusion: Stunting in the Bintang Mountains is strongly influenced by a combination of health service gaps, infectious diseases, socio-cultural factors, and insufficient maternal knowledge. Strengthening maternal Education, improving sanitation, addressing harmful cultural practices, and expanding access to health services are critical strategies to reduce stunting prevalence in highland and resource-limited areas of Indonesia